2010
DOI: 10.1074/jbc.m109.097576
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Voltage- and Store-dependent Calcium Influx on Stretch-induced Differentiation and Growth in Vascular Smooth Muscle

Abstract: Stretch of the vascular wall stimulates smooth muscle hypertrophy by activating the MAPK and Rho/Rho kinase (ROK) pathways. We investigated the role of calcium in this response. Stretch-stimulated expression of contractile and cytoskeletal proteins in mouse portal vein was inhibited at mRNA and protein levels by blockade of voltage-dependent Ca 2؉ entry (VDCE). In contrast, blockade of store-operated Ca 2؉ entry (SOCE) did not affect smooth muscle marker expression but decreased global protein synthesis. Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 36 publications
4
52
0
1
Order By: Relevance
“…In support of this view, we demonstrated first that A10 cells display both SOCE and VOCE, the former being quantitatively larger than the latter, consistent with a proliferative VSMC phenotype (1,2). Interestingly, SOCE activation in VSMC favors immediate-early gene expression and growth whereas VOCE promotes rather VSMC differentiation (40). SOCE in A10 cells resembles the one best characterized in T and RBL cells in the following aspects: (i) It is prevented by classic SOCE antagonists La 3ϩ and 2-APB and the novel antagonist BTP2, (ii) A10 cells express Orai1 and Stim1 recently involved in CRAC in other cell types including VSMCs, (iii) SOCE is important in A10 cell proliferation just as in T cell clonal expansion (13), and (iv) SOCE is tightly modulated by mitochondria because inhibition of mitochondrial Ca 2ϩ uptake prevents this pathway.…”
Section: Discussionsupporting
confidence: 74%
“…In support of this view, we demonstrated first that A10 cells display both SOCE and VOCE, the former being quantitatively larger than the latter, consistent with a proliferative VSMC phenotype (1,2). Interestingly, SOCE activation in VSMC favors immediate-early gene expression and growth whereas VOCE promotes rather VSMC differentiation (40). SOCE in A10 cells resembles the one best characterized in T and RBL cells in the following aspects: (i) It is prevented by classic SOCE antagonists La 3ϩ and 2-APB and the novel antagonist BTP2, (ii) A10 cells express Orai1 and Stim1 recently involved in CRAC in other cell types including VSMCs, (iii) SOCE is important in A10 cell proliferation just as in T cell clonal expansion (13), and (iv) SOCE is tightly modulated by mitochondria because inhibition of mitochondrial Ca 2ϩ uptake prevents this pathway.…”
Section: Discussionsupporting
confidence: 74%
“…cium influx via L-type calcium channels is an important regulator of Rho activity and expression of contractile smooth muscle markers (39,40). We therefore analyzed calcium levels in cells under high and low glucose conditions and found that baseline fluorescence of the Fluo-4 calcium indicator was significantly increased in cells subjected to hyperglycemia (Fig.…”
Section: Calcium Influx Via L-type Calcium Channels Is Involved In Thmentioning
confidence: 99%
“…Actin polymerization is known to regulate smooth muscle differentiation by promoting nuclear translocation of myocardin-related transcription factor, a transcriptional co-activator to serum response factor, which then induces transcription of smooth muscle-specific genes (11). Additionally, activation of the Rho signaling pathway may promote myocardin expression and smooth musclespecific gene transcription via the transcription factor Mef2 (12,13). Because multiple factors can induce Rho/Rho kinase activation, it has been a challenge to dissect those that play a role in stretch-induced smooth muscle differentiation.…”
mentioning
confidence: 99%